Gastric Adenocarcinoma in a Patient with X-Linked Agammaglobulinemia and HIV: Case Report and Review of the Literature - Hajjar, Joud; Hasan, Sana; Forbes, Lisa R.; Hemmige, Vagish; Orange, Jordan S. (Frontiers in Pediatrics, 2016)
X-linked agammaglobulinemia (XLA) is an X-linked inherited disease usually caused by a germline mutation in the BTK gene leading to Bruton’s tyrosine kinase deficiency, which results in the impaired development of B-lymphocytes and a subsequent lack of immunoglobulin production. Patients with XLA have an increased susceptibility to bacterial and viral infections, and multiple case reports have been published regarding an association between XLA and gastrointestinal (GI) malignancy. Here, we describe a case of a 25-year-old man with XLA and HIV, who developed gastric adenocarcinoma. Previously reported cases of XLA and GI malignancy are also reviewed and summarized.